2021
DOI: 10.56093/ijans.v91i8.115927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbal feed additives on intake, rumen fermentation, availability of nutrients and energetic efficiency of feeds in Barbari kids reared under confined condition

Abstract: Weaned male Barbari kids (24) were divided equally into three groups (T1, T2 and T3) to investigate the effect of supplementation of herbal feed additives in the complete pelleted feed on intake of nutrients, rumen fermentation, availability of nutrients and energetic efficiency under stall-fed condition during an eight months feeding trial. Treatments were T1, Concentrate mixture (40%) plus arhar (Cajanus cajan) straw (60%) in Total Mixed Ration (TMR) form fed ad lib.; T2, Concentrate mixture (40%) plus arhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Findings of the present experiment, e.g. digestibility of CP and EE was not influenced by the dietary supplementation of herbal feed additive is also similar to the earlier finding in growing kids in which CP and EE digestibility was not influenced by the dietary supplementation of mixture of herbal feed additive (Chaturvedi et al 2021).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Findings of the present experiment, e.g. digestibility of CP and EE was not influenced by the dietary supplementation of herbal feed additive is also similar to the earlier finding in growing kids in which CP and EE digestibility was not influenced by the dietary supplementation of mixture of herbal feed additive (Chaturvedi et al 2021).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, a nonsignificant effect of tropical tree leaves supplementation as herbal feed additive on dry matter intake (DMI, g/d) was reported in sheep (Malik et al 2017). However, Chaturvedi et al (2021) reported that daily dry matter intake becomes increased due to supplementation of herbal feed additive in growing Barbari kids reared under confined condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation